Penggunaan Media Powerpoint Pada Pembelajaran IPS - Aspiandi, Aspiandi; Buwono, Sri; Wiyono, Hadi; Aminuyati, Aminuyati; Barella, Yusawinur (Peneliti.net, 2025)
This study aims to determine the use of powerpoint media in social studies learning at MTs Yasti Sekuduk and the obstacles in using powerpoint media in social studies learning at MTs Yasti Sekuduk. The form of research used in this research is a qualitative case study method. Informants in this study consisted of vice principals and social studies teachers. Data collection techniques in this study were observation, interviews, and documentation. While the data collection tools are observation guidelines, interview guidelines, and using a camera. The results of this study found: 1) the use of powerpoint media in social studies learning at MTs Yasti Sekuduk, Sambas Regency was rare, and some teachers did not even use powerpoint media. The reason teachers rarely use powerpoint media when studying social studies, teachers find it difficult to make and prepare the media because the teacher's ability is still lacking in understanding powerpoint-based learning media. 2) Obstacles in the use of powerpoint media in Social Studies learning at MTs Yasti Sekuduk, Sambas Regency, namely the lack of teacher knowledge in understanding the use of technology in the form of audio-visual learning media, lack of skills and creativity of teachers who still experience difficulties in making interesting learning media according to the teaching material , it takes a long time to make and prepare the media.